KINERJA PRODUKSI DAN STRATEGI PENGEMBANGAN AGROINDUSTRI KOPI BUBUK DI KOTA BANDAR LAMPUNG - Ayu Maya Sari; Dwi Haryono; Rabiatul Adawiyah (Lampung University, 2017)
This research aims to analyze the production performance and Agroindustry development strategy of coffee powder in Bandar Lampung City. This research is a case study in a coffee powder agroindustry namely Sinar Baru Cap Bola Dunia. Respodents are the owner and employees of the agroindustry. Research data is analyzed by quantitative and qualitative descriptive analysis (analysis of production performance) and descriptive qualitative analysis (SWOT). The results showed that the performance of Sinar Baru Cap Bola Dunia Agroindustry in overall was not in good category. The main priority strategy for developing the agroindustry were (a) utilizing the human resources’ skills to increase production utilizing modern technology, (b) utilizing the human resources’ skills to increase production and government support for increasing sales through exhibitions conducted by department of cooperatives, industry, and trade, (c) utilizing the location near to the sales location there by reducing distribution costs and facilitating the marketing of products to meet the increasing demands of the population, (d) collaborating with the government to facilitate information access related to the agroindustry and promotion abroad, especially to introduce the product in Southeast Asia market through cyberspace or overseas exhibition activities, (e) producing a quality product according to consumers’ tastes for consumers to re-purchase so that it could be competetive to similar competitors.Key words: coffee powder, development strategy, production performance